(untitled) (Encuentros, 2020)
This documentary analysis paper aims to identify in the findings of 57 investigations, the relationship between actions of Corporate Social Responsibility (CSR) and profitability of companies. The NVivo12-Pro software was used for data processing and analysis. The most important findings show that there are positive, negative and neutral relationships, where the positive predominates, which does not depend on the methodological approach with which the research was carried out. This work seeks to provide information for decision makers when implementing or developing CSR management models. Key Words: CSR, companies, profitability, strategy, practices, society.